2016
DOI: 10.1021/acs.macromol.5b02611
|View full text |Cite
|
Sign up to set email alerts
|

Amidine-Mediated Zwitterionic Ring-Opening Polymerization of N-Alkyl N-Carboxyanhydride: Mechanism, Kinetics, and Architecture Elucidation

Abstract: Zwitterionic ring-opening polymerization (ZROP) of Nbutyl N-carboxyanhydrides (Bu-NCAs) has been investigated using 1,8diazabicycloundec-7-ene (DBU), a bicyclic amidine initiator. It was found that poly(N-butylglycine)s (PNBGs) with molecular weight (M n ) in the 3.5−32.4 kg mol −1 range and polydispersity index (PDI) in the 1.02−1.12 range can be readily obtained by systematically varying the initial monomer to initiator feed ratio. The polymerization exhibits characteristics of a controlled polymerization, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 66 publications
1
41
0
Order By: Relevance
“…[15,37,67,68] Bu-NCA similar to NHCs (Scheme 8). [69] The reaction occurs in a controlled manner in low dielectric solvents (eg, THF and toluene), allowing access of polypeptoids having low to medium molecular weights (DP < 300) and narrow PDI (1.02-1.12), similar to what has been reported for NHCs. By contrast, in DMF, only low molecular weight polymers (DP < 40) were formed regardless of the initial monomer to DBU ratios.…”
Section: Synthesis Of Linear Polypeptoidsmentioning
confidence: 64%
See 2 more Smart Citations
“…[15,37,67,68] Bu-NCA similar to NHCs (Scheme 8). [69] The reaction occurs in a controlled manner in low dielectric solvents (eg, THF and toluene), allowing access of polypeptoids having low to medium molecular weights (DP < 300) and narrow PDI (1.02-1.12), similar to what has been reported for NHCs. By contrast, in DMF, only low molecular weight polymers (DP < 40) were formed regardless of the initial monomer to DBU ratios.…”
Section: Synthesis Of Linear Polypeptoidsmentioning
confidence: 64%
“…The cyclic polypeptoid architecture was verified by a combination of end-group analysis with NMR and MS method and AFM and SANS analysis. [69,70] While the ZROP of Bu-NCA using DBU initiators is comparable to that with NHC initiators in rate, DBU has the advantage of being air and moisture stable, in contrast to NHCs. This makes DBU a more robust initiator relative to NHCs towards the ZROP of R-NCAs.…”
Section: Synthesis Of Linear Polypeptoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the driving force of the crystallization of the solvophobic block (PNDG). The same authors also found that cyclic polypeptoids could be prepared by zwitterionic ring‐opening polymerization (ZROP) with 1,8‐diazabicycloundec‐7‐ene (DBU) as an initiator . Beside cyclic homopolymer, that is, poly( N ‐BuGly), random copolypeptoids, poly([ N ‐propargyl glycine]‐ r ‐[ N ‐butyl glycine])s, could also be synthesized by ZROP.…”
Section: Crystallization and Self‐assembly Of Polypeptoid Polymersmentioning
confidence: 99%
“…Typically, two different synthetic strategies toward polypeptoids are possible: iterative submonomer route and ring‐opening polymerization (ROP) of N ‐substituted α‐amino acid‐ N ‐carboxyanhydrides (NNCAs) . Polypeptoids with absolute monodispersity and controlled sequence can be harvested by submonomer approach.…”
Section: Introductionmentioning
confidence: 99%